Bibliometric Analysis on Green Workforce Readiness - Judijanto, Loso (West Science Social and Humanities Studies, 2025)
This study presents a bibliometric analysis of the scholarly literature on green workforce readiness, a critical area in the transition toward sustainable and low-carbon economies. Using data extracted from the Scopus database and analyzed through VOSviewer, the study maps key publication trends, co-occurring themes, leading authors, and international collaboration networks. The results indicate that "sustainable development" serves as the conceptual core of this research domain, with closely linked themes including green economy, workforce training, environmental protection, and green manufacturing. Temporal analysis reveals a shift from foundational concepts like education and environmental policy to more recent emphases on technological and industrial transformations such as renewable energy and circular economy. Author and country collaboration networks underscore the dominance of scholars from the United States, China, and India, alongside increasing contributions from emerging economies. Despite the field's growth, the study identifies research gaps in regional coverage and interdisciplinary integration. The findings offer valuable insights for academics, policymakers, and practitioners aiming to align workforce development strategies with sustainability goals.